Theory of morality and human nature: Why liberal moral theory is the best proposal among other moral theories - Rodríguez Cárdenas, Frank E. (2024)
The present work focuses on the analysis of moral theo- ries and highlights the unique appeal of utilitarianism compared to other ethical currents. What makes opting for utilitarian moral theory interesting? The proposed thesis argues that utilitarianism stands out for its ability to reconstruct and adapt both to human nature and to the constant change of social context. Thus, when this theory has been subjected to criticism, it has demonstrated a remarkable capacity to revise and learn from its mistakes; moreover, it has evolved in its premises to adapt to the complexities of reality, a trait that distinguishes it from other moral theories that fail to maintain their appeal in changing contexts. To support this claim, we will first examine fundamental moral theories and their inherent appeal, then identify inconsistencies in each of them. Next, the validity of utilitarian moral theory will be questioned, but ultimately, the proposed thesis will be justified as a fundamental response.